China's Labor Market Performance and Challenges - Ran, Tao.; Brooks, Ray. (Washington, D.C. : International Monetary Fund, 2003)
A more market-oriented labor market has emerged in China in the past twenty years with growing importance of the urban private sector, as state-owned enterprises have downsized. Despite the progress on reforms, a sizable surplus of labor still exists in the rural sector and state-owned enterprises. The main challenge facing China's labor market in coming years is to absorb the surplus labor into quality jobs while adjusting to World Trade Organization (WTO) accession. This paper estimates that if annual GDP growth averages 7 percent and the employment elasticity is one-half, urban unemployment could double to about 10 percent over the next three to four years. These pressures would be limited by stronger economic growth, especially in the private sector and more labor-intensive service industries which have generated the most jobs in recent years. Therefore, policy should focus on encouraging private sector development while reducing barriers to labor mobility, improving worker skills, upgrading job search services, and strengthening the social safety net.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet